As representações do trabalho de tratamento da loucura e do dispositivo manicomial em o canto dos malditos de Austragésilo Carrano Bueno - Carvalho, Lucas (2022)
The reading of O Canto dos Malditos, by Austragésilo Carrano Bueno, provides us with a rare and important representation of an emblematic period of Brazilian psychiatry: the seventies. The literary work takes us through the story of the narrator character, Austry, committed to the psychiatry hospital when he was only seventeen years old, under the pretext of drug addiction. However, the young man didn’t consider himself addicted or even crazy. The hospitalization was performed compulsorily, without consultation or examination to attest to its need. There, the protagonist is subjected to electroshock and gradually begins to become more and more apathetic and dominated by fear, starting to see himself as crazy. Based on the ontological studies by Lukács, and the studies on power by Foucault, we will analyze the representations of psychiatric treatment work and the psychiatric device in the work in question, as well as its foundations and perspectives.